Juncus roemerianus hemostatic aerogel and preparation method thereof

Through the freeze-thaw and freeze-drying preparation method of rush and PVA, the problems of high cost and poor compatibility of composite aerogels were solved, and low-cost, high-efficiency hemostatic rush hemostatic aerogel was prepared, which has excellent hemostatic effect and good biocompatibility.

CN120733102APending Publication Date: 2025-10-03WUHAN TEXTILE UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510956854.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2025-10-03

AI Technical Summary

Technical Problem

Existing composite aerogels are expensive and have poor compatibility, polysaccharide aerogels have poor mechanical properties, silicon-based aerogels may trigger inflammatory reactions, and composite aerogels have complex components and high costs.

Method used

Juncus rapa hemostatic aerogel was prepared by mixing Juncus rapa and polyvinyl alcohol (PVA) through a freeze-thaw treatment combined with freeze-drying to form a three-dimensional porous network structure with a reasonable cross-linking density, uniform pore distribution, and good cross-linking between Juncus rapa and PVA molecules.

Benefits of technology

The prepared rush hemostatic aerogel has good mechanical strength, hemostatic effect and biocompatibility, low cost, better elastic modulus than chitosan hemostatic aerogel, shortened hemostasis time, and an antibacterial rate of up to 97%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120733102A_ABST
    Figure CN120733102A_ABST
Patent Text Reader

Abstract

The invention provides a juncus roemerianus hemostatic aerogel and a preparation method thereof, and belongs to the field of aerogel preparation, the preparation method comprises the following steps: dissolving PVA in water to prepare a polyvinyl alcohol solution with the concentration of 10-20% wt; grinding the juncus roemerianus subjected to alkali treatment into powder, adding the powder into a polyvinyl alcohol solution, then adding a cross-linking agent solution, and uniformly stirring to obtain a mixed solution; carrying out freeze thawing treatment on the mixed solution for 2-4 times, and then carrying out freeze drying treatment to obtain the juncus roemerianus hemostatic aerogel. The juncus roemerianus and the aerogel material are compounded, a good hemostatic effect is achieved on the basis of low cost, and meanwhile the aerogel dressing has good mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aerogel preparation, and in particular to rush hemostatic aerogel and a preparation method thereof. Background Art

[0002] Aerogel dressings are a new type of wound care material with high air permeability, high swelling capacity, and high absorbency. They can provide a suitable healing environment for wounds and accelerate wound healing. Aerogel dressings can be divided into organic polymer aerogel dressings, inorganic polymer aerogel dressings, and composite aerogel dressings. Organic polymer dressings mainly include polysaccharide aerogel dressings and protein aerogel dressings, while inorganic polymer aerogel hemostatic dressings mainly include silicone-based aerogel dressings. However, polysaccharide aerogel dressings have poor mechanical properties, are fragile, and difficult to operate, limiting their use. The inorganic components contained in silicone-based aerogel dressings can easily cause inflammatory reactions in human tissues that come into contact with them. If they are not properly surface treated, they may irritate surrounding tissue cells, hindering wound healing. Composite aerogel dressings are often complex in composition, which not only makes them relatively expensive, but also some composite aerogels have poor compatibility.

[0003] In the prior art, Chinese patent publication number CN120189549A proposes a multifunctional exosome aerogel dressing and its application. This aerogel dressing uses modified plant cellulose as a matrix, loaded with ginseng-derived exosomes, and then composited with carboxymethyl chitosan. The aerogel is prepared through a directional freezing and freeze-drying process. It exhibits excellent biocompatibility and a lightweight structure. Through rational design, it can simultaneously achieve the triple therapeutic functions of hemostasis, antibacterial treatment, and wound healing. However, the aerogel's composite of ginseng-derived exosomes and carboxymethyl chitosan is relatively expensive.

[0004] In view of this, it is necessary to design a rush hemostatic aerogel and a preparation method thereof to solve the above technical problems. Summary of the Invention

[0005] In view of the technical problems existing in the background technology, the present application provides a rush hemostatic aerogel and a preparation method thereof, aiming to solve the technical problems of high cost of composite aerogels and poor compatibility of some composite aerogels.

[0006] In a first aspect, the present invention provides a method for preparing a rush hemostatic aerogel, comprising the following steps: S1, mixing polyvinyl alcohol (PVA) and water under stirring conditions, standing at room temperature for a period of time, heating in a water bath with stirring to fully dissolve the polyvinyl alcohol, to obtain a polyvinyl alcohol solution with a concentration of 10-20% wt; S2, grinding the alkali-treated rush into powder, mixing it with the polyvinyl alcohol solution obtained in step S1 and stirring it evenly, then adding the crosslinking agent solution, and continuing to stir evenly to obtain a mixed solution; S3, subjecting the mixed solution obtained in step S2 to freeze-thaw treatment 2-4 times, and then freeze-drying the mixed solution to obtain the rush hemostatic aerogel.

[0007] In the technical solution of the embodiment of the present application, PVA is used as the matrix, and after mixing powdered rush with PVA solution, rush aerogel dressing is prepared by freeze-thaw treatment combined with freeze drying. Among them, the most suitable concentration range of PVA solution is 10-20%wt. When the PVA concentration is on the low side, the three-dimensional skeleton composed of rush and PVA is not stable enough, resulting in insufficient strength of the aerogel, prone to collapse, and reduced elastic modulus. When the PVA concentration is on the high side, it will cause the rush and PVA to be cross-linked too densely, the porosity of the aerogel is reduced, and the elastic modulus is reduced.

[0008] In some embodiments, the mass ratio of rush to polyvinyl alcohol is 1:(0.67-1.5).

[0009] In this embodiment, when the rush ratio is too low, the rush powder cannot effectively participate in stress sharing and may also introduce interfacial defects, resulting in a decrease in elastic modulus. At the same time, as a hemostatic functional raw material, too low a rush dosage will also affect the antibacterial and hemostatic properties of the rush aerogel. When the rush ratio is too high, the powder is prone to agglomeration or precipitation, and cannot be evenly distributed in the aerogel, which destroys the continuity of the matrix network, increases the brittleness of the aerogel structure (reduces the elastic modulus), and is prone to breakage during use, thereby weakening the hemostatic effect.

[0010] In some embodiments, in step S3, the freeze-thaw treatment step includes freezing at -(15-20)°C for 12-16 hours, and then taking it out and thawing it at room temperature for 2-4 hours.

[0011] In this embodiment, the freeze-thaw treatment facilitates the formation of a porous physical structure through the nucleation, growth, and melting of ice crystals, significantly improving the mechanical strength, porosity, and stability of the aerogel, making it more suitable for hemostasis. Cyclic freeze-thaw treatment gradually optimizes the microstructure and macroscopic properties of the aerogel structure through multiple physical actions. Large ice crystals are fragmented through repeated crystallization-thawing processes, i.e., the size of the ice crystals is gradually reduced. During the melting process, the ice crystals melt and release some stress, and the polymer chains partially rebound and reorganize, forcing the molecular chains to rearrange to form a more uniform nanofiber network. This also promotes an increase in the density of cross-linking points, ultimately resulting in an aerogel with higher mechanical strength, more uniform structure, and more stable function.

[0012] In some embodiments, in step S3, the temperature of the freeze-drying treatment is -(40-80)°C, and the time of the freeze-drying treatment is 24-72 hours.

[0013] In this example, while the freeze-thaw cycle produced a uniform nanofiber network, a significant amount of water remained within the nanofiber network. If the nanofibers were directly evaporated and dried, the enormous surface tension generated at the gas-liquid interface would pull on the pore walls, causing the optimized nanofiber network to collapse. Freeze-drying rapidly freezes the water into ice before allowing it to sublime directly, eliminating the effects of stress on the aerogel structure. This facilitates physical cross-linking and structural optimization, resulting in a high-strength, high-porosity, low-shrinkage rush aerogel.

[0014] In some embodiments, in step S1, the temperature of the water bath heating and stirring is 80-90°C, and the time is greater than or equal to 30 minutes; in step S1, standing at room temperature for a period of time specifically refers to standing at room temperature for 20-60 minutes.

[0015] In this embodiment, heating the mixture in a water bath to 80-90°C with stirring and maintaining the temperature for ≥30 minutes is primarily to disrupt the crystalline regions of the PVA and overcome intermolecular hydrogen bonds to fully dissolve the PVA. The purpose of standing the mixture at room temperature is to pre-swell the PVA, thereby shortening the subsequent water bath heating time.

[0016] In some embodiments, in step S2, the rush is polished and then sieved using a 300-700 mesh sieve.

[0017] In this embodiment, when the rush powder particle size is too large, the powder will be unevenly distributed in the mixed solution, affecting the uniformity of freeze-drying and reducing the hemostatic effect. At the same time, the large rush powder particle size will also lead to an unstable three-dimensional skeleton structure formed with PVA, reducing the mechanical properties of the aerogel, making it easy to crush, resulting in a lower elastic modulus. The fine rush powder particle size is prone to agglomeration, causing blockage of the aerogel pores, affecting its permeability and elastic modulus, and also causing uneven powder distribution, affecting the hemostatic effect.

[0018] In some embodiments, in step S2, the cross-linking agent is a mixture of citric acid and sodium hypophosphite.

[0019] In some embodiments, the mass ratio of the citric acid to the sodium hypophosphite is (3-1):1.

[0020] In this example, the mixture of citric acid and sodium hypophosphite primarily plays a role in synergistic crosslinking and catalytic esterification in aerogel preparation. The carboxyl groups (-COOH) on the citric acid can form a covalent crosslinked network with the hydroxyl groups (-OH) on PVA or rush through a high-temperature esterification reaction, enhancing the aerogel's skeletal strength. The sodium hypophosphite acts as a reducing agent and catalyzes the esterification, inhibiting the oxidative degradation of citric acid at high temperatures while also accelerating the formation of ester bonds (-COOR) by reducing the activation energy of the esterification reaction, thereby improving crosslinking efficiency.

[0021] In some embodiments, in step S2, the specific steps of alkali treatment include placing the rush in an alkaline solution and heating it for 15-25 minutes, taking it out and washing it with water, then placing it in the alkaline solution again and heating it for 15-25 minutes, taking it out and washing it with water until no alkaline solution remains, then placing it in water and heating it for 10-25 minutes, and drying it.

[0022] In this embodiment, alkali treatment can destroy the hydrophobic lignin and hemicellulose on the surface of rush, and at the same time cause the cellulose chains to swell to expose more polar hydroxyl groups (-OH), thereby increasing the hydrophilicity of rush, promoting the uniform dispersion of rush in PVA solution, and the subsequent cross-linking reaction.

[0023] In a second aspect, an embodiment of the present application provides a rush hemostatic aerogel, which is prepared according to the method for preparing the rush hemostatic aerogel described in any one of the aforementioned technical solutions.

[0024] The beneficial effects of this application are as follows: The present application provides a rush hemostatic aerogel and a preparation method thereof. PVA is used as a matrix, powdered rush is mixed with a PVA solution, and a rush aerogel dressing is prepared by combining freeze-thaw treatment with freeze-drying. The three-dimensional mesh-like porous structure of rush and PVA molecules form a good cross-linking, forming a stable three-dimensional skeleton of the aerogel, so that the elastic modulus of the rush hemostatic aerogel is close to that of the PVA aerogel without additives, and it has good supporting force, flexibility and adhesion, and at the same time has an excellent hemostatic effect. The preparation method provided in the present application directly uses rush powder to prepare hemostatic gauze, without the need for extraction or synthesis, with a simple process and low cost, and has broad prospects for biomedical applications.

[0025] During the preparation process, the present application also regulated the preparation conditions such as the PVA concentration, the mass ratio of rush to PVA, and the particle size of rush powder, so as to obtain an aerogel structure with a reasonable cross-linking density, uniform pore distribution, not easy to break, and uniform rush distribution, thereby balancing its hemostatic and antibacterial properties and mechanical properties. The results showed that when the PVA concentration was 15%, the mass ratio of rush to PVA was 1:1, and the rush particle size was ≤30.8μm (using a 500-mesh sieve), the rush hemostatic aerogel had the best hemostatic effect and mechanical properties. The hemostatic effect and elastic modulus of the rush hemostatic aerogel prepared in this application were better than those of chitosan hemostatic aerogel, with an elastic modulus of 0.22, and the hemostatic time was shortened by about 20s relative to that of chitosan hemostatic aerogel. The antibacterial rate was as high as 97%, and it also had good biocompatibility.

[0026] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] To more clearly illustrate the technical solution of this application, the following is a brief introduction to the drawings used in this application. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be derived from these drawings without inventive effort.

[0028] Figure 1 This is a scanning electron microscope (SEM) image of the rush powder in Example 1 of the present application; Figure 2 Physical pictures of aerogel dressings prepared in Example 1, Example 4 and Comparative Example 2 of the present application; Figure 3 This is a SEM image of the aerogel dressing prepared in Example 1 of the present application; Figure 4 This is an SEM image of the aerogel dressing prepared in Comparative Example 2 of this application; DETAILED DESCRIPTION The following embodiments of the technical solution of the present application will be described in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application and are therefore only examples and are not intended to limit the scope of protection of the present application.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned figure descriptions are intended to cover non-exclusive inclusions.

[0030] In the description of the embodiments of this application, the technical terms "first" and "second" are used only to distinguish different objects and should not be understood to indicate or imply relative importance or implicitly specify the quantity, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "plurality" is more than two, unless otherwise clearly and specifically defined.

[0031] References herein to "embodiments" mean that a particular feature, structure, or characteristic described in connection with the embodiments may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor does it constitute an independent or alternative embodiment that is mutually exclusive of other embodiments. It is understood, both explicitly and implicitly, by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0032] In the description of the embodiments of this application, the term "and / or" is merely a description of the association relationship between associated objects, indicating that three relationships can exist. For example, A and / or B can represent three situations: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this document generally indicates that the associated objects are in an "or" relationship. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of this application can be understood according to specific circumstances.

[0033] Aerogel dressings can be divided into organic polymer aerogel dressings, inorganic polymer aerogel dressings and composite aerogel dressings. Among them, organic polymer dressings mainly include polysaccharide aerogel dressings and protein aerogel dressings, and inorganic polymer aerogel hemostatic dressings mainly include silicon-based aerogel dressings. However, polysaccharide aerogel dressings have poor mechanical properties, are fragile and difficult to operate, and their use is limited. The inorganic components contained in silicon-based aerogel dressings can easily cause inflammatory reactions in human tissues that come into contact with them. If they are not well surface treated, they may irritate surrounding tissue cells and be detrimental to wound healing. The composition of composite aerogel dressings is often more complex, not only are the costs relatively high, but some composite aerogels also have poor compatibility.

[0034] To address the technical issues of high cost and poor compatibility of composite aerogels, this application provides a rush hemostatic aerogel and its preparation method. Using PVA as a matrix, powdered rush is mixed with a PVA solution, and then a rush aerogel dressing is prepared by combining freeze-thaw treatment and freeze-drying. The rush powder exhibits a three-dimensional, porous structure, which facilitates cross-linking with PVA molecules, resulting in an aerogel dressing with excellent mechanical strength. Furthermore, the rush and aerogel material are combined to achieve a good hemostatic effect at a low cost.

[0035] In a first aspect, the present invention provides a method for preparing a rush hemostatic aerogel, comprising the following steps: S1, polyvinyl alcohol (PVA) and water are mixed under stirring conditions, allowed to stand at room temperature for a period of time, and then heated in a water bath with stirring to fully dissolve the polyvinyl alcohol to obtain a PVA solution with a concentration of 10-20%wt.

[0036] S2, grinding the alkali-treated rush into powder, mixing it with the PVA solution obtained in step S1 and stirring it evenly, then adding the crosslinker solution, and continuing to stir evenly to obtain a mixed solution.

[0037] S3, subjecting the mixed solution obtained in step S2 to freeze-thaw treatment 2-4 times, and then freeze-drying the mixed solution to obtain the rush hemostatic aerogel.

[0038] The preparation method provided by the application uses PVA as a matrix. After mixing powdered rush with a PVA solution, a freeze-thaw process and freeze-drying are combined to prepare a rush aerogel dressing. The purpose of standing at room temperature is to pre-swell the PVA, which helps to shorten the time for subsequent water bath heating. The most suitable concentration range of the PVA solution is 10-20%wt. When the PVA concentration is on the low side, the three-dimensional skeleton composed of rush and PVA is not stable enough, resulting in insufficient aerogel strength, prone to collapse, and reduced elastic modulus. When the PVA concentration is on the high side, it will cause the rush and PVA to be too densely cross-linked, the porosity of the aerogel is reduced, and the elastic modulus is reduced.

[0039] In some embodiments, in step S1, standing at room temperature for a period of time specifically refers to standing at room temperature for 20-60 minutes, and heating in a water bath with stirring at a temperature of 80-90° C. for a time greater than or equal to 30 minutes.

[0040] In the technical solution of the embodiment of the present application, the water bath is heated to 80-90°C and stirred and kept at this temperature for ≥30 minutes mainly to destroy the crystalline region of PVA and overcome the intermolecular hydrogen bonding to fully dissolve the PVA. There are strong hydrogen bonds and partial crystalline structures between the PVA molecular chains, which are difficult to be fully penetrated and swelled by water molecules at room temperature. At a temperature of 80-90°C (close to the melting point of PVA), thermal energy can soften the crystalline region and weaken the hydrogen bonds, allowing water molecules to penetrate deep into the polymer chains to achieve swelling, while continuous stirring can provide shear force to accelerate the dispersion of PVA molecules. The treatment time of heating and stirring in a water bath for ≥30 minutes can ensure that the crystalline region of PVA is fully melted to form a uniform, transparent, viscous solution. Too low a treatment temperature or insufficient treatment time will result in incomplete dissolution of PVA, resulting in the final PVA solution containing undissolved particles or gel clumps.

[0041] In some embodiments, in step S2, the alkali treatment comprises placing the rush in an alkaline solution and heating it for 15-25 minutes, removing it and rinsing it with water, then placing it in the alkaline solution again and heating it for 15-25 minutes, removing it and rinsing it with water until no alkaline solution remains, then placing it in water and heating it for 10-25 minutes, and drying it. The alkaline solution can be a sodium hydroxide solution or a potassium hydroxide solution, and the concentration of the alkaline solution is 0.5-2 mol / L. The drying temperature is less than or equal to 65°C.

[0042] In the technical solution of the embodiment of the present application, the hydrophobic lignin and hemicellulose on the surface of rush can be destroyed by alkali treatment, while the cellulose chains are swollen to expose more polar hydroxyl groups (-OH), thereby increasing the hydrophilicity of rush, promoting the uniform dispersion of rush in PVA solution, and the subsequent cross-linking reaction.

[0043] In some embodiments, in step S2, after being polished, the rush is sieved through a 300-700 mesh sieve (powder particle size ≤ 51.3 μm), preferably a 400-600 mesh sieve (powder particle size ≤ 38.5 μm), and further preferably a 500 mesh sieve (powder particle size ≤ 30.8 μm).

[0044] In the technical solution of the embodiment of the present application, when the particle size of the rush powder is too large, the powder will be unevenly distributed in the mixed solution, affecting the uniformity of freeze-drying and resulting in a reduced hemostatic effect. At the same time, the large particle size of the rush powder will also lead to an unstable three-dimensional skeleton structure formed with PVA, reducing the mechanical properties of the aerogel, making it easy to crush, resulting in a reduced elastic modulus. The fine particle size of the rush powder is prone to agglomeration, causing blockage of the aerogel pores, affecting its air permeability and elastic modulus, and also causing uneven powder distribution, affecting the hemostatic effect.

[0045] In some embodiments, in step S2, the crosslinking agent is a mixture of citric acid and sodium hypophosphite. Furthermore, the mass ratio of citric acid to sodium hypophosphite is (3-1):1, preferably 2:1.

[0046] In the technical solution of the embodiment of the present application, the mixture of citric acid and sodium hypophosphite mainly plays a role in synergistic crosslinking and catalytic esterification in the preparation of aerogel. The carboxyl groups (-COOH) on the citric acid can form a covalent crosslinked network with the hydroxyl groups (-OH) on PVA or rush through a high-temperature esterification reaction, thereby enhancing the skeleton strength of the aerogel. The sodium hypophosphite acts as a reducing agent and esterification catalyst, on the one hand inhibiting the oxidative degradation of citric acid at high temperatures, and on the other hand accelerating the formation of ester bonds (-COOR) by reducing the activation energy of the esterification reaction, thereby improving the crosslinking efficiency.

[0047] In some embodiments, the mass ratio of rush to PVA is 1:(0.67-1.5), preferably 1:(0.8-1.2), and further preferably 1:1.

[0048] In the technical solution of the embodiment of the present application, when the ratio of rush is too low, the rush powder cannot effectively participate in stress sharing, and may also introduce interface defects, resulting in a decrease in elastic modulus. At the same time, as a hemostatic functional raw material, too low a rush dosage will also affect the antibacterial and hemostatic properties of the rush aerogel. When the ratio of rush is too high, powder agglomeration or precipitation is likely to occur, and it cannot be evenly distributed in the aerogel, destroying the continuity of the matrix network, increasing the brittleness of the aerogel structure (reducing the elastic modulus), and easily breaking during use, thereby weakening the hemostatic effect.

[0049] In some embodiments, in step S3, the freeze-thaw treatment step includes freezing at -(15-20)°C for 12-16 hours, and then taking it out and thawing it at room temperature for 2-4 hours.

[0050] In the technical solution of the embodiment of the present application, the freeze-thaw treatment is conducive to the formation of a porous physical structure through the nucleation, growth, and melting of ice crystals, significantly improving the mechanical strength, porosity, and stability of the aerogel, making it more in line with the needs of hemostasis. The cyclic freeze-thaw treatment is to gradually optimize the microstructure and macroscopic properties of the aerogel structure through multiple physical actions. The large ice crystals are fragmented through repeated crystallization-thawing processes, that is, the size of the ice crystals is gradually reduced. During the melting process, the ice crystals melt and release some stress, and the polymer chains partially rebound and reorganize, forcing the molecular chains to rearrange to form a more uniform nanofiber network, while promoting the increase in the density of cross-linking points, and ultimately obtaining an aerogel with higher mechanical strength, more uniform structure, and more stable function.

[0051] In some embodiments, in step S3, the freeze-drying treatment temperature is -(40-80)°C, and the freeze-drying treatment time is 24-72 hours.

[0052] In the technical solution of the embodiments of this application, although the cyclic freeze-thaw treatment produces a uniform nanofiber network, a large amount of water is still retained within the nanofiber network. If it is directly evaporated and dried, the huge surface tension generated by the gas-liquid interface will pull on the pore walls, causing the optimized nanofiber network to collapse. Freeze-drying first freezes the water into ice and then directly sublimates it, eliminating the influence of stress on the aerogel structure, facilitating physical cross-linking and structural optimization, and obtaining high-strength, high-porosity, low-shrinkage rush aerogel.

[0053] In a second aspect, an embodiment of the present application provides a rush hemostatic aerogel, which is prepared using any one of the preparation methods in the aforementioned schemes.

[0054] Some specific examples are listed below. It should be noted that the examples described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. Where specific techniques or conditions are not specified in the examples, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used without manufacturer's indication are all commercially available conventional products.

[0055] Example 1 Example 1 provides a method for preparing rush hemostatic aerogel, comprising the following steps: S1. Weigh 35.29 g of 1799 polyvinyl alcohol (PVA) particles into a beaker. Slowly add 200 ml of pure water while stirring. After standing at room temperature for 30 minutes, place the beaker in a water bath at 80-90°C and slowly stir for 30 minutes to fully dissolve the polyvinyl alcohol to obtain a PVA solution with a concentration of 15% by weight.

[0056] S2, put an appropriate amount of rush into an alkaline solution and heat it for about 20 minutes, then take it out and wash it with water, then put it into the alkaline solution again and heat it for 20 minutes, take it out and wash it with water until there is no alkali solution residue, then put it into water and heat it for 20 minutes, take it out and put it into an oven at 60°C to dry it to obtain alkali-treated rush. Grind the alkali-treated rush into powder and sieve it with a 500-mesh sieve to obtain a powder particle size of ≤30.8μm. Mix the rush powder with the PVA solution obtained in step S1 and stir it evenly, wherein the mass ratio of rush to PVA is 1:1, then add the crosslinker solution and continue stirring to obtain a mixed solution. The preparation method of the crosslinker solution is as follows: weigh 0.25g of citric acid and 0.125g of sodium hypophosphite and put them into 2mL of water to fully dissolve them.

[0057] S3, subjecting the mixed solution obtained in step S2 to a freeze-thaw treatment three times. The freeze-thaw treatment involves freezing the solution at -20°C for 12 hours, then thawing the solution at room temperature for 3 hours. This freeze-thaw treatment involves repeating the aforementioned steps three times. The freeze-thawed product is then freeze-dried at -80°C for 48 hours to obtain the rush hemostatic aerogel.

[0058] See Figure 1 The figure shows a scanning electron microscope (SEM) image of rush powder. It can be seen that the rush powder has a three-dimensional network porous structure, which is conducive to forming good cross-linking with PVA molecules to obtain an aerogel dressing with good mechanical strength.

[0059] Example 2-3 The difference between Example 2-3 and Example 1 is that the concentration of PVA in step S1 is 10% (Example 2) and 20% (Example 3), respectively. Other details are the same as in Example 1 and will not be repeated here.

[0060] Examples 4-5 The difference between Examples 4-5 and Example 1 is that the particle size of the rush powder in step S2 is ≤51.3 μm (corresponding to using a 300-mesh sieve, Example 4) and ≤22 μm (corresponding to using a 700-mesh sieve, Example 5). Other details are the same as in Example 1 and will not be repeated here.

[0061] Examples 6-7 The difference between Example 6-7 and Example 1 is that the mass ratio of rush to PVA in step S2 is 1:1.5 (Example 6) and 1.5:1 (Example 7), respectively. The rest is the same as Example 1 and will not be repeated here.

[0062] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that chitosan is used to prepare the aerogel dressing, and the preparation method includes the following steps: 10g of chitosan was added to 90g of a 5% aqueous acetic acid solution and stirred at 30-50°C for 6 hours to dissolve the chitosan. During stirring, air bubbles were removed by ultrasound. Next, 0.5g of glutaraldehyde (a crosslinker) was added to the chitosan-dissolved acetic acid solution and allowed to stand at room temperature for 2-4 hours to form a gel. The solution was then washed with deionized water to a pH of 6-7, freeze-dried at -80°C for 4-12 hours, and finally vacuum-dried for 24-72 hours to obtain the chitosan hemostatic aerogel.

[0063] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that rush is not added to the aerogel, that is, step S2 is deleted, and the PVA solution is directly freeze-thawed in step S3. The rest is the same as in Example 1 and will not be repeated here.

[0064] See Figure 2 The following are photos of aerogel dressings prepared in Example 1, Example 4, and Comparative Example 2, where a is the aerogel dressing prepared in Example 1 (powder particle size ≤ 30.8 μm), b is the aerogel dressing prepared in Example 4 (powder particle size ≤ 51.3 μm), and c is the aerogel dressing prepared in Comparative Example 2 (without rush). It can be seen that the aerogel dressing prepared when the powder particle size is ≤ 30.8 μm has a similar apparent structure to that without rush, while the aerogel dressing prepared when the powder particle size is ≤ 51.3 μm has a rough surface with visible larger powder particles, which are easily crushed and fall off during use.

[0065] See Figures 3 and 4 As shown, Figure 3 This is a scanning electron microscope image of the aerogel dressing prepared in Example 1. Figure 4 This is a scanning electron microscope image of the aerogel dressing prepared in Comparative Example 2. It can be seen that in the aerogel dressing prepared in Example 1, rush particles are evenly dispersed in the PVA. Compared with the aerogel dressing without rush, the three-dimensional network structure of rush in Example 1 plays a certain supporting role in the aerogel, making the pores in the aerogel network structure relatively larger. In contrast, the aerogel dressing without rush has smaller pores and a more compact structure.

[0066] The mechanical properties of the aerogels prepared in Examples 1-7 and Comparative Examples 1-2 were tested. Compression tests of rush aerogels were conducted according to ASTM D1621. The instrument used was an INSTRON 3400 series instrument. The sample was a cylindrical aerogel with a diameter of 15 mm and a height of 30 mm. The loading rate was 5 mm / min. After the test, the aerogel deformation was 80%. During the measurement, the stress-strain curve was observed to ensure smoothness, and the elastic modulus was calculated by curve analysis. The test results are shown in Table 1.

[0067] The hemostatic properties of the aerogels prepared in Examples 1-7 and Comparative Examples 1-2 were tested. Hemostasis experiments adhered to animal ethics standards and used standardized animal models. This experiment employed a rabbit femoral artery injury model. The final experimental data were recorded, including the duration and volume of hemostasis. The coagulation experiment employed a rabbit femoral artery injury model. The main steps involved isolating the rabbit's femoral artery, transecting it by half its diameter, filling the wound with aerogel, and bandaging it. The amount of bleeding was monitored for 180 minutes. The test results are shown in Table 1.

[0068] The antibacterial properties of the aerogels prepared in Examples 1-7 and Comparative Examples 1-2 were tested with reference to the standard GB / T 21551.2-2010. The antibacterial rate was calculated according to the formula: Antibacterial rate (%) = (number of colonies in the control group - number of colonies in the experimental group) / number of colonies in the control group × 100. According to the standard, an antibacterial material is qualified if its antibacterial rate is greater than 90%. The test was conducted using the shaking flask method, and the experimental steps were as follows: 1. Mix 0.1 g of rush aerogel with bacterial suspension (10 mL, 1×10 6 CFU / mL) were placed in a shake flask and shaken (150 rpm) at 37°C for 24 h.

[0069] 2. After dilution, spread on plates, count the colonies, and evaluate the inhibition rate. The test results are shown in Table 1.

[0070] Table 1 As shown in Table 1, the shorter the hemostasis time and the less bleeding, the better the aerogel's hemostatic effect. It can be seen that the hemostatic effect of rush hemostatic aerogel is significantly better than that of chitosan hemostatic aerogel, shortening the hemostasis time by nearly 20 seconds and reducing the bleeding volume by 0.16g. Furthermore, compared to chitosan hemostatic aerogel, the elastic modulus of rush hemostatic aerogel is closer to that of additive-free PVA aerogel. This is because the rush, with its three-dimensional porous network structure, and PVA together form a stable three-dimensional skeleton. The appropriate crosslinking density and pore distribution give the rush hemostatic aerogel good support and flexibility. If the elastic modulus is too low, the aerogel's ability to adapt to soft tissue deformation will be weakened, making it difficult to adhere closely to the wound surface. At the same time, the adhesion will be weakened, and the feel will become harder, affecting the user experience.

[0071] Comparing Examples 1-7, it can be seen that when the PVA concentration is 15%, the mass ratio of rush to PVA is 1:1, and the rush particle size is ≤30.8 μm (using a 500-mesh sieve), the rush hemostatic aerogel has the best hemostatic effect and mechanical properties. This is because: First, when the PVA concentration is low (Example 2), the three-dimensional skeleton composed of rush and PVA is not stable enough, resulting in insufficient strength of the aerogel, easy collapse, and reduced elastic modulus; when the PVA concentration is high (Example 3), the rush and PVA will be too densely cross-linked, the porosity of the aerogel will be reduced, and the elastic modulus will be reduced.

[0072] Secondly, when the powder particle size of rush is too large (Example 4), the powder will be unevenly distributed in the mixed solution, affecting the uniformity of freeze-drying and reducing the hemostatic effect. At the same time, the large rush powder will also reduce the mechanical properties of the aerogel, making it easy to crush and reduce the elastic modulus. The fine rush powder particle size (Example 5) is prone to agglomeration, causing blockage of the aerogel pores, affecting its permeability and elastic modulus, and also causing uneven powder distribution, affecting the hemostatic effect.

[0073] Third, when the rush ratio is low (Example 6), the rush powder cannot effectively participate in stress sharing and may also introduce interface defects, resulting in a slightly lower elastic modulus than Example 1. At the same time, as a hemostatic functional raw material, too low a rush dosage will also affect the antibacterial and hemostatic properties of the rush aerogel. When the rush ratio is high (Example 7), the powder is prone to agglomeration or precipitation, and cannot be evenly distributed in the aerogel, which destroys the continuity of the matrix network, increases the brittleness of the aerogel structure (reduces the elastic modulus), and is prone to breakage during use, thereby weakening the hemostatic effect.

[0074] The blood and cell compatibility of the aerogel prepared in Example 1 was tested according to ISO 10993-4 and ISO 10993-5, wherein the hemolysis rate was required to be ≤10% and the cell survival rate was required to be ≥75%. The cytotoxicity test procedures were as follows: 1. Extraction solution preparation: aerogel was prepared at a surface area / volume ratio of 3 cm 2 / mL was extracted in serum-containing culture medium at 37℃ for 72h.

[0075] 2. Cell culture: Inoculate L929 mouse fibroblasts and culture in the extract for 24-48 hours.

[0076] 3. Detection method: MTT assay was used to determine cell viability.

[0077] Blood compatibility was assessed using the intravenous implantation method. The aerogel catheter was implanted into the rabbit's ear vein. Blood was collected regularly to measure platelet count, coagulation function, and hemolysis rate. The test results are shown in Table 2.

[0078] Table 2 As shown in Table 2, the cell survival rate of the rush aerogel dressing prepared in Example 1 was 94%, and the hemolysis rate was 3.7%, indicating that it had good biocompatibility.

[0079] In summary, the present application provides a method for preparing rush hemostatic aerogel, in which PVA is used as a matrix, powdered rush is mixed with a PVA solution, and a rush aerogel dressing is prepared by combining freeze-thaw treatment with freeze-drying. During the preparation process, the present application also regulates the preparation conditions such as the PVA concentration, the mass ratio of rush to PVA, and the particle size of rush powder, so as to obtain an aerogel structure with a reasonable cross-linking density, uniform pore distribution, not easy to break, and uniform rush distribution, thereby balancing its hemostatic and antibacterial properties and mechanical properties. The results show that when the PVA concentration is 15%, the mass ratio of rush to PVA is 1:1, and the rush particle size is ≤30.8μm (using a 500-mesh sieve), the rush hemostatic aerogel has the best hemostatic effect and mechanical properties.

[0080] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing rush hemostatic aerogel, characterized in that: The steps include: S1, mixing polyvinyl alcohol and water under stirring conditions, standing at room temperature for a period of time, heating in a water bath and stirring to fully dissolve the polyvinyl alcohol to obtain a polyvinyl alcohol solution with a concentration of 10-20%wt; S2, grinding the alkali-treated rush into powder, mixing it with the polyvinyl alcohol solution obtained in step S1 and stirring it evenly, then adding the crosslinking agent solution, and continuing to stir evenly to obtain a mixed solution; S3, subjecting the mixed solution obtained in step S2 to freeze-thaw treatment 2-4 times, and then freeze-drying the mixed solution to obtain the rush hemostatic aerogel.

2. The method for preparing the rush hemostatic aerogel according to claim 1, characterized in that: The mass ratio of rush to polyvinyl alcohol is 1:(0.67-1.5).

3. The method for preparing the rush hemostatic aerogel according to claim 1, characterized in that: In step S3, the freeze-thaw treatment step includes freezing at -(15-20)°C for 12-16 hours, and then taking it out and thawing it at room temperature for 2-4 hours.

4. The method for preparing the rush hemostatic aerogel according to claim 1, characterized in that: In step S3, the temperature of the freeze-drying treatment is -(40-80)°C, and the time of the freeze-drying treatment is 24-72 hours.

5. The method for preparing the rush hemostatic aerogel according to claim 1, characterized in that: In step S1, the temperature of the water bath heating and stirring is 80-90°C, and the time is greater than or equal to 30 minutes; in step S1, standing at room temperature for a period of time specifically refers to standing at room temperature for 20-60 minutes.

6. The method for preparing the rush hemostatic aerogel according to claim 1, characterized in that: In step S2, the rush is polished and then sieved through a 300-700 mesh sieve.

7. The method for preparing the rush hemostatic aerogel according to claim 1, characterized in that: In step S2, the cross-linking agent is a mixture of citric acid and sodium hypophosphite.

8. The method for preparing the rush hemostatic aerogel according to claim 7, characterized in that: The mass ratio of the citric acid to the sodium hypophosphite is (3-1):

1.

9. The method for preparing the rush hemostatic aerogel according to claim 1, characterized in that: In step S2, the specific steps of alkali treatment include placing the rush in an alkali solution and heating it for 15-25 minutes, taking it out and washing it with water, then placing it in the alkali solution again and heating it for 15-25 minutes, taking it out and washing it with water until no alkali solution remains, then placing it in water and heating it for 10-25 minutes, and drying it.

10. A rush hemostatic aerogel, characterized in that: The rush hemostatic aerogel is prepared according to the preparation method of rush hemostatic aerogel according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Multi-effect functional exosome aerogel dressing and application thereof

    CN120189549A